Mongolia : Raising Female Participation in the Large Scale Mining Sector - Khan, Tehmina (World Bank, Washington, DC, 2014)
As Mongolia has begun to develop its abundant mineral resources over the past decade, the share of mining in gross domestic product (GDP) has more than tripled to around 20 percent currently. The sector has also contributed up to a third of total government receipts in recent years and more than 80 percent of exports in 2010. Evidence suggests that women tend to miss out on the potential benefits associated with a booming mining sector. In addition, large scale mines typically tend to be the dominant employers in remote locations. The policy note starts by gauging potential growth and employment effects associated with the expansion of the mining sector on other sectors, using a computable general equilibrium model specially calibrated for the Mongolian economy. It then considers experience and lessons from other countries that are trying to integrate and ensure the participation of women in large-scale mining and the practical policy recommendations to do so. The key findings are that there is a high degree of occupational segmentation in the mining sector, with women mostly located in service support roles, although this is by no means unique to Mongolia. However in Mongolia's case, this segmentation also likely reflects Mongolian labor regulations that existed until 2008 and which limited women s participation in the sector. Evidence from around the world indicates that gender equal laws are a necessary and crucial first step towards guaranteeing gender equality and equity, but by themselves are not sufficient. Companies may also consider revising recruitment or hiring strategies with the objective of raising the share of female employment across all professional categories in the mining sector.